SIMULATION MODEL SCHEDULING QUEUE IN TELLER BANK WITH MULTI CHANNEL – MULTI PHASE - Fitri Firdalius (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
Progress in improving communication and information, as well as the increasingly rapid development of the banking world, requires a customer service system capable of providing satisfying services to customers. One of the problems that often arise in banking customer service systems is customer queuing services which cause customers to wait too long to get service. Information alone is not enough if it cannot be managed to be the best alternative, therefore a simulation system for scheduling bank customer queues is used. The design of the queue simulation model is expected to provide Mega Padang bank management information and better service to customers, so that every input, process and output that occurs during model development and simulation can be seen. Therefore, the simulation is carried out using the discrete event method. The customer service system of Bank Mega Padang which produces services explains the effect and behavior of the observed system, in this case it provides information about the average customer waiting time, the average customer waiting time and the length of time that tellers are unemployed for a certain period. time. The results of the system design process from time to time can increase teller unemployment by as many as 65 Bank Mega Padang customers. This study maximizes service time to customers based on the duration of service provided by the teller so that there are no unemployed or unserved terllers. The research that was achieved for the management of Bank Mega Padang was that management did not need a teller due to a lot of time. idle cashier